KEBIJAKAN MORATORIUM PENGIRIMAN TENAGA KERJA KE LUAR NEGERI DAN DAMPAKNYA TERHADAP PENINGKATAN KUALITAS PEKERJA MIGRAN INDONESIA - Prihanto, Purwaka Hari (Jurnal Paradigma Ekonomika, 2013)
The objectives of this reseach are to analyse the impact of the Indonesia moratorium migrant workers sending policy toward the growth of Indonesia migrant workers and the upgrade of migrant workers quality. This study was done in Indonesia, using the time series data from year 2005 to 2012. To analyse the data used linier regression with helped SPSS program. The results of study showed that in periode of observation, the Indonesia migrant workers decline average 4.15 percent, with the highest decline of Indonesia migrant workers growth are workers who works in Malaysia and Arabian Saudi. The regression model was founded that the Indonesia moratorium migrant workers sending policy have the impact in reduce the Indonesia migrant workers in Informal Sector, but not yet have the impact to upgrade the quality of migrant workers.Keywords : Indonesian migrant workers, Moratorium migrant workers sending policyHalaman